The significance of Stanniocalcin 2 in malignancies and mechanisms. Issue 1 (1st January 2021) - Li, Shasha; Huang, Qian; Li, Dongliang; Lv, Lizhi; Li, Yi; Wu, Zhixian
ABSTRACT: Human stanniocalcin 2 (STC2) is an ortholog of fish stanniocalcins (STCs) and is widely expressed in various organs and tissues. The gene is localized on chromosome 5q33 or 5q35. STC2 has been implicated in glucose homeostasis and phosphorus metabolism. It is also reported to be implicated in various malignancies. STC2 was found to be implicated in breast cancer and gynecologic cancers, suggesting hormone-specific or -dependent activities in these malignancies. Moreover, it was reported to be involved in gastrointestinal tumors, including esophageal, gastric, colorectal, and liver cancers, and respiratory cancers, including laryngeal and lung cancers. It also influenced renal carcinoma and prostate cancer. Notably, as a secreted phosphoprotein, STC2 was detectable in serum and possessed promising predictive value in several malignancies. This review aims to improve the understanding of the role of STC2 in patient diagnosis and prognosis, and tumor development and progression, as well as the mechanisms involved.